Nogle Forsøgsstationer i Tyskland, Holland, Belgien og Frankrig. Rejsenotitser. - Tuxen, C. F. A. (Tidsskrift for Landøkonomi, 2018)
Nogle Forsøgsstationer i Tyskland, Holland, Belgien og Frankrig. Rejsenotitser.